Copper effect on photosynthetic performance, symbiotic efficiency and biosorption of rhizobia associated with Horse gram [Macrotyloma uniflorum (Lam.) Verdc.] - Edulamudi, Prabhavati; Zakkula, Vishnuvardhan; Rao Vanga, Umamaheswara; Mallaiah Konada, Veera (Cuban Journal of Agricultural Science, 2019)
The aim of the present study was to evaluate the ability of Copper (Cu) tolerance in rhizobia and enhancing the photosynthetic performance, symbiotic efficiency and biosorption potential in the rhizobia inoculated Horse gram [Macrotyloma uniflorum (Lam.) Verdc.] plants. Four rhizobial strains HGR-4, 6, 13, 25 grown under different concentrations of Copper (Cu) were inoculated individually to Horse gram plants. Among them, Horse gram plants inoculated with the strain HGR-4 have shown enhanced PN values up to 500 μg g-1 of Cu concentration. Nodulation was maximum upon inoculation with HGR-6 at 300 μg g-1 of Cu and inoculation with HGR-4, 13 and 25 at 100 μg g-1. The amount of leghaemoglobin was maximum in the Horse gram plants inoculated with the strain HGR-13 at 500 μg g-1 of Cu. Biosorption potential of the strain HGR-6 (GQ483458 Rhizobium sp., ATCC 2336) was determined by Atomic Absorption Spectroscopy (AAS). It has shown maximum biosorption of Cu both in nodules and also in soil samples. This study demonstrates that the Cu tolerant rhizobia i.e. HGR-4, 6, 13 and 25 enhanced the photosynthetic performance, pod formation, symbiotic efficiency and biosorption potential. Hence, Horse gram plants associated with rhizobia could be used effectively in phytoremediation of metal (Cu) contaminated soils. Key words: Biosorption, metal toxicity, phytoremediation, rhizobia.